2018
DOI: 10.1371/journal.pone.0193277
|View full text |Cite
|
Sign up to set email alerts
|

In vivo screening platform for shiga toxin-producing Escherichia coli (STEC) using Caenorhabditis elegans as a model

Abstract: Shiga toxin-producing Escherichia coli (STEC) strains are the main cause of bacillary dysentery, although STEC strains generally induce milder disease symptoms compared to Shigella species. This study aimed to determine the virulence of STEC using the nematode Caenorhabditis elegans as a model host. Worm killing, fertility and bacterial colonisation assays were performed to examine the potential difference in the virulence of STEC strains compared to that of the control E. coli OP50 strains on which worms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Future opportunities could be to enlarge the panel of pathogens studied. The study of Hwang et al (174) demonstrated that C. elegans is an effective model to examine and compare the pathogenicity and virulence variation of STEC strains (24 strains tested) to that of E. coli OP50 strain. White and Herman (80) demonstrated the merit of a C. elegans approach in the identification of novel genes that are involved in combating the emerging nosocomial bacterial pathogen Stenotrophomonas maltophilia infection.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Future opportunities could be to enlarge the panel of pathogens studied. The study of Hwang et al (174) demonstrated that C. elegans is an effective model to examine and compare the pathogenicity and virulence variation of STEC strains (24 strains tested) to that of E. coli OP50 strain. White and Herman (80) demonstrated the merit of a C. elegans approach in the identification of novel genes that are involved in combating the emerging nosocomial bacterial pathogen Stenotrophomonas maltophilia infection.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Future opportunities could be to enlarge the panel of pathogens studied. The study of Hwang et al ( 174 ) demonstrated that C . elegans is an effective model to examine and compare the pathogenicity and virulence variation of STEC strains (24 strains tested) to that of E .…”
Section: Translational Research and Prospectsmentioning
confidence: 99%
“…Fertility is also reduced upon exposure to Shiga toxin-producing Escherichia coli (SHEC) strains. [60,61] In fact, the dramatic fertility suppression induced by C. neoformans has been used as a rapid screening measure to identify conserved, virulence-determining pathogen genes. [62] Thus, fertility is responsive to immune perturbations and impacts are pathogen specific.…”
Section: Immunity-fertility Tradeoffs Are Explicitly Demonstrated In mentioning
confidence: 99%
“…STEC is one of the six major classifications (pathotypes) of diarrheagenic E. coli . This differentiation depends on medical syndromes, symptoms, epidemiology, the presence of antigen type Stx1 and Stx2 virulence factors, and interaction with epithelial cells ( Hwang et al., 2018 ). Infection with most types of enteropathogenic E. coli causes watery diarrhea ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many enteric infections lead to a short-lived dysfunction of the gastrointestinal system. In extreme cases, a severe disorder can occur based on specific pathogenic infections such as that with STEC ( Bron et al., 2017 ; Hwang et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%